Evaluasi Efektivitas Iklan Aero Street di Media Sosial dengan Consumer Decision Model (CDM) - Mardiani, Eri; Rasyad, Rizky Zakariyya; Hasian, Irene (Jurnal EMT KITA, 2024)
Social media advertising plays a crucial role in marketing. This research evaluates the influence of advertising messages and Brand recognition on consumer Attitudes on social media, using the Consumer Decision Model (CDM) on Aero Street advertising. A total of 100 respondents were selected through purposive sampling. Data was collected through questionnaires and analyzed using multiple linear regression. The results show that the advertising message variables (I, Information) and Brand recognition (B, Brand recognition) have a positive effect on consumer Attitudes (A, Attitude), such as A = 2.172 + 0.229F + 0.258B. The calculated F statistical test is 19.005, exceeding the F table of 3.090, indicating a significant joint influence. The advertising message and Brand recognition variables simultaneously and partially have a significant effect on consumer Attitudes, showing the effectiveness of Aero Street advertising on social media with CDM.